A giant dermoid cyst in the floor of the mouth: a case report - Thirunavukarasu, Yuvaraj; Roy, Biswanath; Arya, Ajaykumar; Pari, Vishnupriya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Dermoid cysts are slow-growing cystic masses that are lined by stratified squamous epithelium and contain skin appendages. Dermoid cysts in the floor of the mouth account for less than 0.01% of all neck and oral cavity cysts. They can be either congenital or acquired. We report a case of a 25-year-old male, a final-year engineering student, who came to our outpatient department with complaints of swelling in the mouth and weight loss for 4 years. On examination, a large cystic swelling in the floor of the mouth, approx. 5x6 cm, obscuring the oropharynx, was seen. USG and CECT of the neck suggested ranula and plunging ranula in the right submandibular space, respectively. He underwent a combined (debulking and enucleation) submandibular cystic swelling excision through a transoral approach under general anesthesia guided by awake fiber optic nasal intubation. The intraoperative and postoperative periods were uneventful. Histopathologic examination of the resected tissue specimen suggested a dermoid cyst. The patient recovered well during the 1-month follow-up, and he gained weight up to 2.5 kg in a month of treatment. Dermoid cysts are very rare cystic lesions on the floor of the mouth. Surgery is the most curable method of treatment. A proper clinical examination with imaging guidance is necessary for accurate delineation of the cyst. Large submandibular cystic lesions can be excised by combining debulking and enucleation through a transoral approach, with a good cosmetic and functional outcome.